DOI: 10.22215/etd/2022-15311
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Thermal Energy Storage in Buried Water Tanks for Single Detached Houses

Abstract: Seasonal thermal energy storage (STES) could allow solar energy to offset the majority of building energy loads in cold climates. This thesis outlines one of the first long-term, full-scale experimental studies on seasonal storage at the single-detached home scale. A solar thermal system couples a large evacuated tube solar array to both short term thermal storage tanks and a 36 m 3 buried water tank used for seasonal storage. Solar heat stored in these water tanks provides space heating (SH) and domestic hot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(25 citation statements)
references
References 99 publications
(179 reference statements)
1
24
0
Order By: Relevance
“…Nonetheless, previous experiments and simulations at CHEeR showed that such glazing levels can still cause winter overheating. A 4.38% ratio of south-facing glazing to conditioned floor area was used during this experiment which was significantly lower than the 8% used in Meister's experiment [7]. The shading configuration for this experiment is detailed in Table 3.2.…”
Section: Windows and Window Shadingmentioning
confidence: 99%
See 4 more Smart Citations
“…Nonetheless, previous experiments and simulations at CHEeR showed that such glazing levels can still cause winter overheating. A 4.38% ratio of south-facing glazing to conditioned floor area was used during this experiment which was significantly lower than the 8% used in Meister's experiment [7]. The shading configuration for this experiment is detailed in Table 3.2.…”
Section: Windows and Window Shadingmentioning
confidence: 99%
“…However, these experiments faced challenges due to faulty solar collectors and issues with the data acquisition system which resulted in an incomplete data set. Despite these setbacks, CHEeR managed to achieve a solar fraction of 68% [7].…”
Section: Existing Contributionsmentioning
confidence: 99%
See 3 more Smart Citations